Pozycja i rola tłumacza jako biegłego w postępowaniu sądowym Wybór orzecznictwa krajowego i Unii Europejskiej - Berezowski, Łukasz Jan (Translatoryka i Translacje. Przekład w XXI wieku. Wyzwania – możliwości – trendy, 2020)
The following study aims at outlining several fundamental case-law decisions provided for by national [Polish] and EU law relating to the participation of a translator or an interpreter in the judicial proceedings involving foreigners (acting as both defendant or injured party). All quoted rulings issued by common courts, Polish Supreme Court and the European Court of Justice extend applicability of the rules of substantive law in Poland (including criminal procedure code and legislation on the common court regime) with regard to the role and position of a translator or an interpreter. The motivation standing behind those decisions is focused on enabling the party with no command of the language of procedure to act comprehensively before the court as well as to be supplied with adequate assistance guaranteed by both domestic and international law.